2011
DOI: 10.1073/pnas.1104494108
|View full text |Cite
|
Sign up to set email alerts
|

Functional prokaryotic–eukaryotic chimera from the pentameric ligand-gated ion channel family

Abstract: Pentameric ligand-gated ion channels (pLGICs), which mediate chemo-electric signal transduction in animals, have been recently found in bacteria. Despite clear sequence and 3D structure homology, the phylogenetic distance between prokaryotic and eukaryotic homologs suggests significant structural divergences, especially at the interface between the extracellular (ECD) and the transmembrane (TMD) domains. To challenge this possibility, we constructed a chimera in which the ECD of the bacterial protein GLIC is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
116
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(131 citation statements)
references
References 37 publications
14
116
1
Order By: Relevance
“…They do not impair the allosteric coupling, but certainly modulate the functional properties. For instance, we showed that performing the F119Y and M121F mutations on Lily results in an acceleration of the desensitization kinetics (16). Extensive mutagenesis work has shown that the entire interface is involved in fine tuning of the allosteric response to agonist (18,19).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They do not impair the allosteric coupling, but certainly modulate the functional properties. For instance, we showed that performing the F119Y and M121F mutations on Lily results in an acceleration of the desensitization kinetics (16). Extensive mutagenesis work has shown that the entire interface is involved in fine tuning of the allosteric response to agonist (18,19).…”
Section: Resultsmentioning
confidence: 99%
“…Coordinates and structure factors were deposited in the Protein Data Bank (PDB) with PDB ID 4X5T. Whole-cell and single-channel patch-clamp electrophysiology was performed as previously described (16). Details are provided in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 (see also Table 1). Note that the proton binding sites for GLIC activation are located primarily in the ECD (47), although an intramembranous His residue on M2 is essential (45,48). Given the long distance between the sites of mutation and the agonist (proton) binding sites, the shifts in ligand sensitivity likely reflect changes in the ability to couple agonist binding to channel gating.…”
Section: Glic M4mentioning
confidence: 99%
“…Furthermore, their remarkable sensitivity to alcohols, general anesthetics, and other clinically relevant compounds (11,12) make them attractive targets for drug design. Remarkably, chimeras of GLIC with other eukaryotic members of the LGIC family retain the functional properties of the individual domains, strongly suggesting that the pathway for allosteric communication is essentially conserved across prokaryotic and eukaryotic channels (13,14).…”
mentioning
confidence: 99%